Online shopping innovative behavior: A review from consumers perspectives - Mohd Suki, Norazah; Ahmad, Mohd. Ismail; Thyagarajan, Venu (2005)
Online shopping has shift the consumer paradigm from shopping at the brick and mortar stores to click and mortar stores that has directed the consumer to experienced innovative online behavior in electronic retailing.Existing studies ignored several other important factors that can affect consumers’ decision to purchase product and service from the Internet.For example, the role of consumers’ innovativeness has not been investigated despite its importance.Drawing from the Technology Acceptance Model, Technology Planned Behavior and Diffusion Innovation Theory, this study extended the models by incorporating online shopper innovative behavior and exogenous factors and applies it to the online shopping context.